Comparing the Efficacy of Local Corticosteroid Injection, Platelet-Rich Plasma, and Extracorporeal Shockwave Therapy in the Treatment of Pes Anserine Bursitis: A Prospective, Randomized, Comparative Study - Wesam Gouda; Awad S. Abbas; Tarek M. Abdel-Aziz; Mohamed Z. Shoaeir; Walid Ahmed; Abdelhfeez Moshrif; Ahmed Mosallam; Mohamed Kamal (Advances in Orthopedics)
Background. Pes anserine bursitis (PAB) is one of the most common causes of painful knee syndromes. This study aimed at examining the efficacy of local corticosteroid injection, platelet-rich plasma (PRP) injection, and extracorporeal shock wave therapy (ESWT) as different modalities to alleviate pain and enhance function in patients with pes anserine bursitis (PAB). Methods. A prospective, randomized, comparative study was conducted on 180 patients diagnosed with chronic PAB. They were equally divided into three groups as follows: Group I received a local corticosteroid injection of 40 mg of methylprednisolone acetate/1 ml; Group II received a PRP injection; and in Group III, ESWT was used. Outcome measures included the visual analog scale (VAS), Western Ontario and McMaster Universities (WOMAC) pain score, WOMAC physical function score, and Ritchie articular index (RAI) for tenderness, which were recorded at the baseline, after 1 week, and after 8 weeks. Results. Before the application of procedures, there was a statistically significant increase in the WOMAC pain score in the local corticosteroid group compared to the PRP group and the ESWT group (P<0.001). After the application of procedures, there was a statistically significant improvement in the 1-week and 8-week WOMAC pain score, WOMAC physical function score, and VAS in the local corticosteroid group in comparison to the PRP group and the ESWT group. (P<0.001). Moreover, RAI for tenderness shows statistically significant improvement at 8 weeks in the local corticosteroid groups compared to the PRP groups (P<0.001) and ESWT groups (P<0.001). Similarly, a statistically significant difference was found between the PRP and ESWT groups (P=0.023). Conclusion. Our data suggest that in patients with PAB, local corticosteroid injection is more efficient than PRP injection and ESWT for reducing pain and enhancing function.